2018
DOI: 10.3390/su10124342
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Shared Mobility

Abstract: In a wider understanding, shared mobility can be defined as trip alternatives that aim to maximize the utilization of the mobility resources that a society can pragmatically afford, disconnecting their usage from ownership. Then, shared mobility is the short-term access to shared vehicles according to the user’s needs and convenience. The contributions and added value of this paper are to provide an up-to-date and well-structured review on the area of shared mobility to researchers and practitioners of the tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
101
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(105 citation statements)
references
References 85 publications
(116 reference statements)
1
101
0
3
Order By: Relevance
“…Today, there is a significant positive psychological change toward shared mobility. This has partly been encouraged through sharing economy models in mobility, which has facilitated new transport solutions such as car sharing, ride sharing, bike sharing, and ride sourcing [39][40][41].…”
Section: Social Impacts: Benefits and User Acceptance Of Fmod Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Today, there is a significant positive psychological change toward shared mobility. This has partly been encouraged through sharing economy models in mobility, which has facilitated new transport solutions such as car sharing, ride sharing, bike sharing, and ride sourcing [39][40][41].…”
Section: Social Impacts: Benefits and User Acceptance Of Fmod Systemsmentioning
confidence: 99%
“…B2C is referred to as free-floating car-sharing, where users are not required to return the car to the pick-up location (i.e., a one-way trip is allowed). While P2C is where existing car owners rent their vehicles to others for a short period of time [41,46].…”
Section: Car-sharingmentioning
confidence: 99%
“…As information and communication technology (ICT) including the technologies, products, and applications that facilitate mobile internet access [1] has rapidly developed, the relationship between transportation and communications has been extensively discussed in the transportation area e.g., [1][2][3]. In the long-term perspective, their relationship can affect sustainable urban development in various ways [4].…”
Section: Introductionmentioning
confidence: 99%
“…VSSs are frequently included in a wider urban planning strategy, often highlighting changed parking norms, to densify and reduce the number of parking spaces. Collaboration between construction companies, property owners, housing associations, municipalities and private actors has been pointed out as crucial to develop well-functioning concepts [8][9][10]. VSS and BSS (Bike-sharing systems) are often set up in pilot projects which reflects a recent trend of viewing cities as innovative sites for sustainability transitions [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…In an overview of shared mobility, Machado et.al. [10] found that many users of mobility services are environmentally concerned and familiar with technological devices. The authors highlight that users put high demands on reliable, flexible, available, attractive and comfortable transport solutions that are not too expensive.…”
Section: Introductionmentioning
confidence: 99%